2013
DOI: 10.1371/journal.pntd.0002307
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin-like Helminth Defence Molecules (HDMs): Absence of Cytotoxic, Anti-microbial and Anti-protozoan Activities Imply a Specific Adaptation to Immune Modulation

Abstract: Host defence peptides (HDPs) are expressed throughout the animal and plant kingdoms. They have multifunctional roles in the defence against infectious agents of mammals, possessing both bactericidal and immune-modulatory activities. We have identified a novel family of molecules secreted by helminth parasites (helminth defence molecules; HDMs) that exhibit similar structural and biochemical characteristics to the HDPs. Here, we have analyzed the functional activities of four HDMs derived from Schistosoma manso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 105 publications
(125 reference statements)
2
43
0
Order By: Relevance
“…For example, the mammalian, but not the helminth, peptides displayed potent bactericidal activity (Thivierge et al, 2013). In addition, mammalian peptides were cytotoxic to macrophages at concentrations above 10 M, whereas the helminth peptides had no detectable deleterious effects on the cells, even at concentrations of 50 M (Thivierge et al, 2013). Accordingly, we proposed that despite having a similar structure, the distribution of positive charge across the peptides might distinguish the helminth and mammalian peptides, and confer different biological activities to each.…”
Section: Inhibition Of Antigen Processingmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, the mammalian, but not the helminth, peptides displayed potent bactericidal activity (Thivierge et al, 2013). In addition, mammalian peptides were cytotoxic to macrophages at concentrations above 10 M, whereas the helminth peptides had no detectable deleterious effects on the cells, even at concentrations of 50 M (Thivierge et al, 2013). Accordingly, we proposed that despite having a similar structure, the distribution of positive charge across the peptides might distinguish the helminth and mammalian peptides, and confer different biological activities to each.…”
Section: Inhibition Of Antigen Processingmentioning
confidence: 91%
“…On the other hand, comparative studies of the mammalian HDPs and parasite HDMs revealed clear differences in their in vitro biological activities. For example, the mammalian, but not the helminth, peptides displayed potent bactericidal activity (Thivierge et al, 2013). In addition, mammalian peptides were cytotoxic to macrophages at concentrations above 10 M, whereas the helminth peptides had no detectable deleterious effects on the cells, even at concentrations of 50 M (Thivierge et al, 2013).…”
Section: Inhibition Of Antigen Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…CatL1 and GST have been shown to activate dendritic cells via interaction with the pattern recognition receptor (PRR) Toll-like receptor 4 (TLR4) (15). F. hepatica and other helminth-derived peptides have also shown to suppress the activation of macrophages by microbial stimuli and to alter the response of B cells to cytokine stimulation (17,18). Total ESPs and recombinant versions of thioredoxin peroxidase have been shown to induce the alternative activation of macrophages in murine (14,19) and ruminant (16,20) models of fascioliasis.…”
mentioning
confidence: 99%
“…Cathepsin L1 has also been shown to cleave CD4 from the surface of lymphocytes [9] and prevent antibody-dependent cell cytotoxicity (ADCC) from killing newly excysted juvenile (NEJ) parasites [10]; one of the few mechanisms known to kill NEJs. More recently Donnelly and colleagues have shown multiple modes of immunosuppression involving a family of helminth defence molecules, similar to host defence peptides that are capable of suppressing macrophage activation and B-cell cytokine responses [11]; providing evidence parasite for mimicry.…”
Section: Introductionmentioning
confidence: 99%